Dix ans de pratiques des concours d’architecture en France : bilan et perspectives - Élise Macaire; Jodelle Zetlaoui-Léger (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère, 2019)
This article presents the key findings of a study of a decade of architecture competitions practice in France. In the first part, it reports on the evolution of the use of this procedure compared to others, based on statistics of public tender notices published between 2006 and 2015. Then, based on the results of different surveys, the article analyses the points of view on this procedure expressed by project clients, programmers, architects and engineers, and elaborates on the key factors they mention: the mobilizing character of competitions; access to commissions; candidate selection procedures; the level of services required; approaches to notions of cost, quality and innovation; programming; research progressiveness. In fine the article presents several recommendations co-elaborated by the different research protagonists and aimed at improving the procedure as well as creating a partner monitoring system to inform public policy. Architecture Competition, Public Project Management, Architectural Design, Architects, Evaluation of Public Policy